2020
DOI: 10.21608/sjas.2020.37530.1033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity for Some Egyptian Wheat Varieties based on Morphological Characters and SSR Markers

Abstract: The genetic diversity estimates can be useful in important genotypes selection for plant breeders. Eight durum and three bread wheat cultivars were used to study and compare morphological traits with molecular study using SSR technique based genetic diversity estimates. Significant and highly significant differences among wheat genotypes were observed for all traits except flag leaf attitude and outer glume pubescence. Highly significant differences were obtained between durum and bread wheat genotypes for mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Overall, the B and D genomes have more diversity in drought tolerance than the A genome. This finding agrees in part with recent findings by Jaiswal et al [63], El-Rawy [64], and El-Rawy and Hassan [11], who reported substantial genetic diversity among wheat genotypes in the B genome.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, the B and D genomes have more diversity in drought tolerance than the A genome. This finding agrees in part with recent findings by Jaiswal et al [63], El-Rawy [64], and El-Rawy and Hassan [11], who reported substantial genetic diversity among wheat genotypes in the B genome.…”
Section: Discussionsupporting
confidence: 93%
“…Considering all the other markers, a total of 30 alleles were detected, which ranged from 2 ( DuPw115 ) to 6 ( Xgwm155 ) (see Supporting information, Tables S1 and S2). Xgwm155 resulted the most polymorphic marker, as also observed in previous studies 37‐39 . Among the durum wheat varieties, Nadif and Marco Aurelio appeared to be the most similar (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Xgwm155 resulted the most polymorphic marker, as also observed in previous studies. [37][38][39] Among the durum wheat varieties, Nadif and Marco Aurelio appeared to be the most similar (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations